Effects of Global and Regional Dust Storms on the Martian Hot O Corona and Photochemical Loss. Issue 4 (27th March 2020) - Lee, Yuni; Fang, Xiaohua; Gacesa, Marko; Ma, Yingjuan; Tenishev, Valeriy; Mahaffy, Paul; Dong, Chuanfei; Combi, Michael; Bougher, Stephen; Jakosky, Bruce
Abstract: We examine here for the first time the effects of both global and regional dust storms on the formation of the Martian hot O corona and associated photochemical loss of O. Our study is conducted by utilizing our integrated model framework, which couples our Martian hot O corona model with a multifluid magnetohydrodynamic model for Mars for the dusty and clear atmospheric condition cases. We present our results with the most up‐to‐date cross sections for the O( 3 P )‐CO2 collisions. The main effect of dust storms on the ionosphere is the upward shift of the ionosphere on the dayside, which results in an increase in production of hot O at all altitudes above the ionospheric peak. However, the dust‐induced inflation of the neutral upper atmosphere results in an enhancement in collisional loss of hot O and thus effectively suppresses the hot O density, reducing the global photochemical loss rate by 28% for the global dust storm scenario. The relative density structure of the hot O corona does not show any significant changes, while its magnitude decreases at all altitudes. Key Points: We investigated the effect of dust storms on photochemical escape from Mars using up‐to‐date cross sections for O‐CO2 collisions The storm‐induced upward shift of the ionosphere causes increased production of hot O and efficient thermalization occurs by the inflated thermosphere The net result is a global photochemical escape rate that is suppressed by 28% during the global dust storm scenario